Optimizacija CNC tehnologije pri izdelavi umetniškega izdelka - Remic, Katarina (Les (Ljubljana), 2020)
The work analyses the optimization of the manufacturing process of an artistic wooden product (mirror frame) with a 3-axis CNC machine. The 3D model was first made in ArtCAM, from where the STL file was later uploaded to SolidWorks. The parameters for the HSR (high speed roughing), and HSM (high speed machining) operations were determined in SolidCAM. The findings show that a combination of operations from HSR and HSM group are the best choice, considering the shape of the model and the capabilities of the machine, as the best ratio between the quality of the surface and the time needed for the operation is provided by these. Operations differ with regard to the tool path and parameters that can be adjusted. The operations were compared and the best results are achieved when the HSR operations "Contour Roughing" and then "Rest Roughing" are used and when the HSM operation "3D Constant Step Over" is used, where the machining time amounted 4 hours and 1 minute. Finally the G code was made for our product.
Keywords: CNC; furniture; les; milling; pohištvo; rezkanje; SolidCAM; SolidWorks; wood